On the scalar $π K$ form factor beyond the elastic region - Frederic Noël, Leon von Detten, Christoph Hanhart, Martin Hoferichter, Bastian Kubis (SciPost Physics Proceedings)
Pion-kaon ($π K$) final states, often appearing in heavy-particle decays at the precision frontier, are important for Standard-Model tests, to describe crossed channels with exotic states, and for spectroscopy of excited kaon resonances. We construct a representation of the $π K$ $S$-wave form factor using the elastic $π K$ scattering phase shift via dispersion relations in the elastic region and extend this model into the inelastic region using resonance exchange, while maintaining unitarity and the correct analytic structure. As a first application, we successfully described the $τ → K_S π ν_τ$ spectrum to not only achieve a better distinction between $S$- and $P$-wave contributions, but also to provide an improved estimate of the $CP$ asymmetry produced by a tensor operator as well as the forward-backward asymmetry, both of which can be confronted with future data at Belle II. The work presented here is published in [L. von Detten et al., Eur. Phys. J. C 81, 420 (2021)].